2018
DOI: 10.1039/c7cp07472g
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative electron attachment and anion-induced dimerization in pyruvic acid

Abstract: We report partial cross sections for the dissociative electron attachment to pyruvic acid. A rich fragmentation dynamics is observed. Electronic structure calculations facilitate the identification of complex rearrangement reactions that occur during the dissociation. Furthermore, a number of fragment anions produced at electron energies close to 0 eV are observed, that cannot originate from single electron-molecule collisions. We ascribe their production to secondary reactions of the transient anions with neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…[11] Zawadzki et al observed anion-molecule reactions in as imilar crossed-beam quadrupole mass spectrometer arrangement to that used herein, in which the pressure wasb etween one and two orders of magnitude higher,b ut also in aD EA time-of-flightm ass spectrometer,i n which considerably lower pressures had to be used due to the multi-channel plate detector present in the chamber. [11] Zawadzki et al observed anion-molecule reactions in as imilar crossed-beam quadrupole mass spectrometer arrangement to that used herein, in which the pressure wasb etween one and two orders of magnitude higher,b ut also in aD EA time-of-flightm ass spectrometer,i n which considerably lower pressures had to be used due to the multi-channel plate detector present in the chamber.…”
Section: Dea To 3bpmentioning
confidence: 64%
See 4 more Smart Citations
“…[11] Zawadzki et al observed anion-molecule reactions in as imilar crossed-beam quadrupole mass spectrometer arrangement to that used herein, in which the pressure wasb etween one and two orders of magnitude higher,b ut also in aD EA time-of-flightm ass spectrometer,i n which considerably lower pressures had to be used due to the multi-channel plate detector present in the chamber. [11] Zawadzki et al observed anion-molecule reactions in as imilar crossed-beam quadrupole mass spectrometer arrangement to that used herein, in which the pressure wasb etween one and two orders of magnitude higher,b ut also in aD EA time-of-flightm ass spectrometer,i n which considerably lower pressures had to be used due to the multi-channel plate detector present in the chamber.…”
Section: Dea To 3bpmentioning
confidence: 64%
“…Nevertheless,t his fragment is only detected in DEA to 3BP.Avibronic (non-adiabatic) coupling between the n!p*( involving the Br lone pair) and p!p*s tates is possible because the energies are very close to each other.T he fragment ions HCOO À ,O À and OH À are also formed through core excited resonances peaking at around5eV.T hese fragments are also observed in DEA to pyruvic acid, [11] and therefore, can be associated with transitions from the oxygen lone pair or p orbitals. However,a ccording to calculations, the n!p*t ransition is essentially dark due to an egligible oscillator strength.…”
Section: Dea To 3bpmentioning
confidence: 97%
See 3 more Smart Citations